2018
DOI: 10.4314/tjpr.v17i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Traditional uses, phytochemistry and biological activities of <i>Cotula cinerea</i> Del: A review

Abstract: Cotula cinerea Del. belongs to the family Asteraceae. It is widely used in the traditional medicinal system for the treatment of various ailments such as colic, cough, diarrhea, digestive disorders, rheumatism, urinary and pulmonary infections, fever and headaches. Cotula cinerea contains a wide range of phytochemical compounds such as saponins, essential oils, tannins, flavonoids, steroids, and terpenoids. This paper reviews information pertaining its traditional uses, phytochemistry and biological activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The results discussed above indicated that Cotula cinerea extracts contained several phenolic phytochemicals including phenolic acids, flavonoids, and sulfated flavonoids. While the occurrence of phenolic acid derivatives and flavonoids has been previously reported, to the best of our knowledge, this is the first report of sulfated flavonoids in Cotula cinerea extracts. Given the various biological activities attributed to such compounds in the last decade, including anticoagulant, antiplatelet, antiviral, anti‐inflammatory, immunomodulatory and antitumor properties, their presence in this plant will obviously play an important positive role in its biological activities and will make this plant an open research area for further investigations.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…The results discussed above indicated that Cotula cinerea extracts contained several phenolic phytochemicals including phenolic acids, flavonoids, and sulfated flavonoids. While the occurrence of phenolic acid derivatives and flavonoids has been previously reported, to the best of our knowledge, this is the first report of sulfated flavonoids in Cotula cinerea extracts. Given the various biological activities attributed to such compounds in the last decade, including anticoagulant, antiplatelet, antiviral, anti‐inflammatory, immunomodulatory and antitumor properties, their presence in this plant will obviously play an important positive role in its biological activities and will make this plant an open research area for further investigations.…”
Section: Resultsmentioning
confidence: 58%
“…Among the non-glycosylated detected flavonoids, the quercetin derivatives chrysospenol-D (6), chrysosplenetin (7), oxyayanin-B (8), axillarin (9) and 3-methylquercetin (10), which have all been previously reported in Cotula cinera extracts, 5,6,9 were also detected in these samples. The structures of these compounds were readily assigned through a combination of their UV-vis spectra and highresolution mass spectra in addition to the subsequent MS/MS product ions which were in agreement with the proposed structures and the previously reported data for the proposed compounds.…”
Section: Flavonoidsmentioning
confidence: 61%
See 3 more Smart Citations